Factors associated with antibiotic administration delay among preterm infants with late-onset bloodstream infection. (February 2022) - Baczynski, M.; Kharrat, A.; Zhu, F.; Ye, X.Y.; Shah, P.S.; Weisz, D.E.; Jain, A.
Summary: Early antibiotic administration is an important modifiable factor in reducing mortality from late-onset bloodstream infections in preterm infants. In a cohort study including 142 infants with non-coagulase negative staphylococcus bloodstream infection at two tertiary neonatal intensive care units, we identified typical practice-related factors that may be targeted to prevent delays in antibiotic administration. Collection of cerebrospinal fluid or urine sample before administering antibiotics, a longer time taken to site a peripheral intravenous catheter among those without pre-existing access, and a longer time taken to administer fluid boluses were associated with a longer than median time to antibiotic administration.